ANALISIS PERBEDAAN KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN EMPLOYEE STOCK OPTION PLAN (ESOP) PADA PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Riyani Safitri Rumain; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
AbstractThis research was conducted with the aim to determine the differences in companyperformance and company value before and after the implementation of employeestock option plan (ESOP) in companies listed on the Indonesia stock exchange for theperiod 2015-2017. This type of research is an event study. The population in thisstudy were all companies listed on the Indonesian stock exchange, the sampletechnique used was purposive sampling. Based on the specified criteria, the sampleobtained in this study amounted to 6 companies. The data analysis method used inthis study was a non-parametric test, the Wilcoxon signed rank test. The conclusionof this study shows that (1) there is no difference in company performance asmeasured by abnormal returns before and after the application of the employee stockoption plan. (2) there are differences in company values measured by PBV before andafter the application of the employee stock option plan.Keywords: employee stock option plan, company performance (abnormal return),company value (PBV).